Emotional Congruence With Children Is Associated With Sexual Deviancy in Sexual Offenders Against Children. (September 2017) - Hermann, Chantal A.; McPhail, Ian V.; Helmus, L. Maaike; Hanson, R. Karl
Emotional congruence with children is a psychologically meaningful risk factor for sexual offending against children. The present study examines the correlates of emotional congruence with children in a sample of 424 adult male sexual offenders who started a period of community supervision in Canada, Alaska, and Iowa between 2001 and 2005. Consistent with previous work, we found sexual offenders against children high in emotional congruence with children were more likely to be sexually deviant, have poor sexual self-regulation, experience social loneliness, and have more distorted cognitions about sex with children. Overall, our findings are most consistent with a sexual deviancy model, with some support for a blockage model.